The interactive effects of Easyzyme and phytase in diets containing high-fiber co-products on growth performance of nursery pigs - Graham, A.B.; Nitikanchana, S.; De Jong, J.A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Two experiments were conducted to determine the effects of a dietary non-starch polysaccharide enzyme (Easyzyme, Archer Daniels Midland Co., Decatur, IL) or phytase (Phyzyme, Danisco Animal Nutrition, St. Louis, MO) addition in corn-soybean meal or high-fiber diets on nursery pig growth performance. In Exp. 1, 192 nursery pigs (PIC 327 × 1050, initially 21.8 lb) were allotted to 1 of 4 dietary treatments arranged in a 2 × 2 factorial. Main effects were diet type (corn-soybean meal or corn-soybean meal plus 30% wheat middlings) with or without added dietary enzyme (Easyzyme Mixer 1, 1 lb/ton). Each experiment involved 6 pigs per pen and 8 replications per treatment. All diets contained 340.5 phytase units (FTU)/lb. From d 0 to 21, pigs fed corn-soybean meal diets had greater (P < 0.001) ADG than those fed diets containing 30% wheat midds. Added Easyzyme had no effect on ADG. ADFI and F/G exhibited a diet type × Easyzyme interaction (P < 0.03). In corn-soybean meal diets, Easyzyme had no effect on ADFI or F/G, whereas in diets containing 30% wheat midds, Easyzyme increased ADFI and worsened F/G.
Keywords: Swine; By-products; Enzyme; Fiber; Phytase; Nursery pig